Exploring Two Student’s Group Perception of BIM Course in an Indonesia Vocational Higher Institution - Abdi Suryadinata Telaga; Thyana Adhesa Avianto (Faculty of Engineering, Universitas Negeri Yogyakarta, 2025)
Building information modelling (BIM) utilization in architecture construction and engineering (ACE) companies in Indonesia is growing. BIM has been seen to have benefit in reducing cost and shortening building construction time. However, lack of BIM skilled workforce hamper BIM adoption in AEC companies in Indonesia. Therefore, questionnaire has been developed and distributed to student to measure perception about BIM course. Nineteen five-likert scale questions were developed to measure student perception about student computer skill background, benefit of BIM knowledge for future career, material quality, time allocated, and benefit of exam and assignment. The questionnaires were distributed to two group of student that are student worker and regular student. The data were analyzed using descriptive statistics and Welch's t-test to compare the perceptions of the two groups. The study found no significant difference in perceptions between student workers and regular students. These insights can help refine the BIM curriculum to better align with industry requirements. The groups were selected whether the student workers had different perception about the course compare to regular student.